P0170 Trastuzumab for HER2-positive breast cancer: Experience from a middle-income Asian country. (July 2015) - Ho, G.F.; Mastura, M.Y.; Kaur, R.P.; Hoo, L.P.; Lim, T.O.
Abstract : Background: Trastuzumab has been available in Malaysia for 20 years. However, the vast majority of patients, even those with stage I–III disease, have limited access to the treatment. This could be because, in the absence of a reliable registry, policy makers and health professionals are ill informed of the poor survival outcome in the local population and the potential effect of modern therapies to improve outcome. Patients would naturally seek treatment when they could afford to pay for it, thus creating a natural experiment to explore the effect of trastuzumab in this population. Methods: We identified 189 HER2-positive breast cancer patients with sufficient data from a cohort previously enrolled in an observational study to evaluate cancer care performance in 2011–12. 39 (21%) of these patients were treated with trastuzumab while 150 (79%) were not. We use Cox proportional hazards model to estimate the effect of trastuzumab on overall survival. Prognostic covariates included were age, stage, and tumour size. Findings: The median age of the patients was 52 years; 36% was aged <50 years, almost all paid for their care out-of-pocket. 65% of patients had early breast cancer, 20% locally advanced breast cancer and 4% metastatic breast cancer. Overall, treatment with trastuzumab was associated with a 35% improvement in survival, though this was not statistically significant. This corresponded to 12% improvement in survival at 5 years for locally advanced breast cancer and 15% for metastatic breast cancer. Interpretation: Trastuzumab treatment in a routine setting is associated with better survival outcome but this could not be statistically demonstrated as too few patients were treated in this population.